A compliant and secure IT infrastructure for the National Library of Greece in consideration of internet security and GDPR - Vavousis, Konstantinos; Papadopoulos, Marinos; Polley, John; Xenakis, Christos (Qualitative and Quantitative Methods in Libraries, 2020)
The application of the General Data Protection Regulation (GDPR) is considered an issue of vital importance for the smooth operation of IT infrastructures, especially for companies in EU Member States. GDPR is a useful tool, which, among other requirements, mandates the adoption of privacy-by-design and advanced security techniques. Taking into account its requirements, this article analyses their implementation with regard to applied Internet Security solutions. While the Regulation offers a minimum set of technical Internet Security means to be taken into consideration by companies and organizations to achieve GDPR compliance, the current paper aims to highlight the adaptation of strong security mechanisms that will not only set companies compliant with GDPR, but also maintain them strong and secure against most threats.